Climate response to stratospheric aerosol injection during the Harmattan season in West Africa - Francis Nkrumah; Gandome Mayeul Leger Davy Quenum; Kwesi A Quagraine; Simone Tilmes; Nana Ama Browne Klutse; Atanas Dommo; Hubert A Koffi; Patrick Essien; Rebecca Bediako (Environmental Research: Climate)
Stratospheric Aerosol Injection (SAI), a proposed climate intervention, aims to reduce the amount of solar radiation reaching the Earth’s surface by increasing the reflectivity of the atmosphere, thereby offsetting the warming effect of greenhouse gases. During the Harmattan season (December–February) in West Africa (WA), a natural meteorological phenomenon injects dust and sand particles into the atmosphere, leading to a cooling effect. In this study, we investigate the influence of SAI on West African surface temperature, dust, and other meteorological variables using the Whole Atmosphere Community Climate Model under the Shared Socioeconomic Pathway 2-4.5 scenario and the Assessing Responses and Impacts of Solar Climate Intervention on the Earth system with SAI (ARISE-SAI) dataset. Our findings indicate that SAI intervention significantly impacts the projected surface temperatures, specific humidity, and wind speed changes during the Harmattan season. Compared to a future without SAI, the intervention shows a significant net cooling effect over most parts of WA during the mid-future period (2050–2069). Also, SAI intervention significantly decreases moisture content over southern and northern WA in the near-future (2035–2054), mainly due to the net cooling effects over WA, when compared to a future without SAI. This feature is enhanced in the mid-future period. The cooling effects of SAI are likely to reduce the air’s capacity to hold moisture, leading to lower specific humidity levels relative to a future without SAI. It could also have negative implications, such as increased aridity compared to a future without SAI in the northern and central regions of WA. These findings also highlight the potential for SAI to improve air quality in certain areas but also underscore the need for careful consideration of implementation strategies and possible trade-offs. The changes from SAI observed are specific to the ARISE simulation and may differ from other SAI simulations.